The Yin and Yang of SagS: Distinct Residues in the HmsP Domain of SagS Independently Regulate Biofilm Formation and Biofilm Drug Tolerance - Jozef Dingemans (American Society for Microbiology, 2018)
ABSTRACT The formation of inherently drug-tolerant biofilms by the opportunistic pathogen Pseudomonas aeruginosa requires the sensor-regulator hybrid SagS, with ΔsagS biofilms being unstructured and exhibiting increased antimicrobial susceptibility. Recent findings indicated SagS to function as a switch to control biofilm formation and drug tolerance independently. Moreover, findings suggested the periplasmic sensory HmsP domain of SagS is likely to be the control point in the regulation of biofilm formation and biofilm cells transitioning to a drug-tolerant state. We thus asked whether specific amino acid residues present in the HmsP domain contribute to the switch function of SagS. HmsP domain residues were therefore subjected to alanine replacement mutagenesis to identify substitutions that block the sensory function(s) of SagS, which is apparent by attached cells being unable to develop mature biofilms and/or prevent transition to an antimicrobial-resistant state. Mutant analyses revealed 32 residues that only contribute to blocking one sensory function. Moreover, amino acid residues affecting attachment and subsequent biofilm formation but not biofilm tolerance also impaired histidine kinase signaling via BfiS. In contrast, residues affecting biofilm drug tolerance but not attachment and subsequent biofilm formation negatively impacted BrlR transcription factor levels. Structure prediction suggested the two sets of residues affecting sensory functions are located in distinct areas that were previously described as being involved in ligand binding interactions. Taken together, these studies identify the molecular basis for the dual regulatory function of SagS. IMPORTANCE The membrane-bound sensory protein SagS plays a pivotal role in P. aeruginosa biofilm formation and biofilm cells gaining their heightened resistance to antimicrobial agents, with SagS being the control point at which both pathways diverge. Here, we demonstrate for the first time that the two distinct pathways leading to biofilm formation and biofilm drug tolerance are under the control of two sets of amino acid residues located within the HmsP sensory domain of SagS. The respective amino acids are likely part of ligand binding interaction sites. Thus, our findings have the potential not only to enable the manipulation of SagS function but also to enable research of biofilm drug tolerance in a manner independent of biofilm formation (and vice versa). Moreover, the manipulation of SagS function represents a promising target/avenue open for biofilm control.